Life insurance agents face new challenges due to the Committee on Efficient Distribution of Life Insurance (CEDLI) regulations. Volume I of II. - Lim, Sin Mian. (2008)
This report investigates the challenges that life insurance agents face due to Committee on Efficient Distribution of Life Insurance (CEDLI) regulations.